Kualitas Produk, Persepsi Harga dan Online Customer Review terhadap Keputusan Pembelian pada E-Commerce Shopee di Kota Semarang - Ashila Choirunnida; Rokh Eddy Prabowo (IPM2KPE, 2024)
This research aims to partially analyze the influence of product quality, price perceptions and online customer reviews on purchasing decisions. The research population was Shopee e-commerce users in Semarang City with a sample of 96 respondents who were determined using a purposive sampling technique. Primary data was obtained through a questionnaire, then processed with the help of the SPSS 23 program. The research results showed that the research instrument was declared valid and reliable. The coefficient of determination test (R2) was 41.8, which means that simultaneously the ability of the independent variables to influence purchasing decisions was 41.8 percent. The F test results were 23.703 with a significance level of 0.000 < 0.05, which means that this research model is feasible and can be analyzed further. Conclusion, that product quality has a positive and significant effect on purchasing decisions on Shopee e-commerce. Price perception has a positive and significant effect on purchasing decisions on Shopee e-commerce. Keywords: Product Quality, Online Customer Reviews, Price Perception